Unveiling the impact of competition weight loss on gut microbiota: alterations in diversity, composition, and predicted metabolic functions - Driuchina, Anastasiia; Isola, Ville; Hulmi, Juha J; Salmi, Vera M; Hintikka, Jukka; Ahtiainen, Juha P; Pekkala, Satu (Informa UK Limited, 2025)
Background
Competitive sports and sports nutrition, popular among amateur athletes aiming for a lean physique, have limited research on gut microbiota.
Methods
We conducted a 46-week study to analyze the consequences of fat loss and diet restrictions in 23 fitness athletes who prepared for a physique competition. Body composition, dietary intakes, serum cytokines and chemokines, and fecal samples were analyzed.
Results
Fat loss through caloric restriction and aerobic exercise led to an increased phylogenetic diversity of gut microbiota and changes in the composition of gut microbiota, with Faecalibacterium, Lachnospiraceae, Bacteroides, and Intestinimonas showing altered abundances. Fat loss also changed the predicted microbial functions responsible for the metabolism of carbohydrates and amino acids. Consumption of energy, carbohydrates, fiber, vitamins and minerals, and various fatty acids decreased during the preparation for the competition, which was partly associated with changes in gut microbiota. Several cytokine levels decreased (IL1a, IL1b, IL10, and TFNα), and certain chemokine levels increased (GROa and RANTES). During the 23-week regain period after the competition, gut microbiota showed signs of recovery, with increased diversity compared to pre- and post-competition measurements. Most taxonomic changes returned to their baseline levels after the regain period.
Conclusions
The study highlights the dynamic nature of gut microbiota and its response to fat loss and regain in non-obese fitness/physique competitors and provides novel insights into how competitive sports and sports nutrition can influence the gut ecosystem.